2016
DOI: 10.1007/s10182-016-0277-9
|View full text |Cite
|
Sign up to set email alerts
|

Information content of partially rank-ordered set samples

Abstract: Partially rank-ordered set (PROS) sampling is a generalization of ranked set sampling in which rankers are not required to fully rank the sampling units in each set, hence having more flexibility to perform the necessary judgemental ranking process.The PROS sampling has a wide range of applications in different fields ranging from environmental and ecological studies to medical research and it has been shown to be superior over ranked set sampling and simple random sampling for estimating the population mean. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Otherwise, we have subsetting error and this PROS sample is called imperfect. To model an imperfect PROS sampling design, following [1,15] and [16], let α be a double stochastic misplacement probability matrix,…”
Section: Pros Sampling Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Otherwise, we have subsetting error and this PROS sample is called imperfect. To model an imperfect PROS sampling design, following [1,15] and [16], let α be a double stochastic misplacement probability matrix,…”
Section: Pros Sampling Designmentioning
confidence: 99%
“…He also showed that PROS sampling has some advantages over RSS. [15] and [16] showed that the Fisher information of PROS samples is larger than the Fisher information of RSS samples of the same size. Since 2011, PROS sampling design has been the subject of many studies.…”
Section: Introductionmentioning
confidence: 96%
“…For more information, see Chen et al 9 and Hatefi and Jafari Jozani. 10 Table 8 summarizes the averages, SDs and the percent SD reductions ofp mp relative top srs under different ranking models. Table 9 provides similar results forp reg , the multi-concomitant RSS estimator which uses the logistic regression models for the ranking purpose.…”
Section: Breast Cancer Data Analysismentioning
confidence: 99%
“…Nazari et al [9] have estimated the distribution function using PROS samples. Hatefi et al [10] have studied the information and uncertainty structures of PROS data.…”
Section: Introductionmentioning
confidence: 99%